Data Wrangling - Using Pandas, SQL, and Java - Campesato, Oswald (Mercury Learning and Information, 2023)
This book is intended primarily for those who plan to become data scientists as wellas anyone who needs to perform data cleaning tasks. It contains a variety of features of NumPy and Pandas and how to create databases and tables in MySQL. Chapter 7 covers many data wrangling tasks using Python scripts and awk-based shell scripts. Companion files with code are available for downloading from the publisher.Features: Provides the reader with basic Python 3, Java, and Pandas programming concepts, and an introduction to awk Includes a chapter on RDBMs and SQL Companion files with code